IMMUNOINFLAMMATORY RHEUMATIC DISEASES ASSOCIATED WITH TYPE I INTERFERON: NEW EVIDENCE - E. L. Nasonov; A. S. Avdeeva (Научно-практическая ревматология)
Immunoinflammatory rheumatic diseases (IIRDs) are a large group of pathological conditions with impaired immunological tolerance to autogenous tissues, leading to inflammation and irreversible organ damage. The review discusses current ideas on the role of type I interferons in the immunopathogenesis of IIRDs, primarily systemic lupus erythematosus, and new possibilities for personalized therapy.